Embracing the Era of Artificial Intelligence: The Transformation of Education in Indonesia from Primary School to Higher Education - Soelistiono, Soegianto; Hamid, Rabiatul Adawiyah; Wahidin (Global Writing Academica Researching & Publishing, 2024)
The digital revolution driven by the rapid advancement of artificial intelligence (AI) compels the education system in Indonesia to undergo transformation in order to prepare future generations who not only understand technology but also possess the ability to utilize it wisely and innovatively. Indonesian education must adopt approaches that are relevant to the demands of the times, emphasizing the development of skills that enable effective interaction with this intelligent technology. This article examines various strategic steps to prepare Indonesian education for the AI era, ranging from primary school to higher education. The primary focus of this discussion is the formulation of curricula that align with future needs, enhancement of foundational skills necessary for interacting with AI, and fostering ethical understanding in the use of this technology. This study also recommends policies that could improve access to AI-based education, particularly in remote areas, by optimizing teacher and student training to harness the potential of AI in supporting more efficient and inclusive learning processes. By effectively integrating technology at every educational level, Indonesia can produce a generation better prepared to face global challenges and contribute to the development of technology-based solutions.